Efeito duradouro da solução hipertônica sobre o tamanho dos quanta na junção neuromuscular de camundongos com deficiência do transportador vesicular de acetilcolina - Wallace Lucio de Camargo (2015)
After application of hypertonic solution to synapses, there is a long lasting increase in neurotransmitter release, as evidenced by an increase in the size of miniature endplate potentials (MEPPs). The increase in quantal size was interpreted as being due to increased incorporation of the acetylcholine into readily available to release vesicles in a process dependent of the vesicle acethylcholine transporter (VAChT). This process was called vesicle second stage loading. Our goal was to test this hypothesis using non pharmacological tools, in order to study the participation of VAChT in this long lasting changes in neurotransmission. We used neuromuscular preparations from genetically modified C57BL male mice with reduced VAChT expression (KDVAChT). We used animals at two different ages to evaluate the temporal development of second stage loading. To measure MEPPs, we used the current clamp technique. We recorded about 100 MEPPs during 300 seconds at five different fibers of each animal, before and after treatment with hypertonic solution (NaCl 234mM). To measure the MEPCs, we used the voltage clamp technique and a similar sampling protocol. We did not detect significant differences between WT and KDVAChT in MEPP size before and after treatment with hypertonic solution. In WT 3 months old animals hypertonic treatment increased MEPPs from 1.13 ± 0.19 to 1.55 ± 0.13 mV (n = 9) and in KDVAChT it increased from 0.79 ± 0, 09 mV to 1.21 ± 0.11 mV (n = 5). In 12 months old animals hypertonic treatment increased MEPP amplitude from 1.29 ± 0.14 mV to 1.69 ± 0.15 mV (n = 11) and in KDVAChT it increased from 0.98 ± 0, 14 mV to 1.75 ± 0.15 mV (n = 9). We did not observe significant differences in the size of MEPCs between WT and KDVAChT mice, when recorded before hypertonic stimulation. MEPCs size in WT animals was 3.02 ± 0.19 nA, n = 3, while in KDVAChT animals it was 2:57 ± 0:23 nA, n = 4. We conclude that reducing VAChT did not change second stage loading, which suggests that VAChT is not the target of hypertonic solution effect, or there may be unknown mechanisms to compensate vesicular filling in reduced VAChT animals.